1975
DOI: 10.2307/1964718
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to Family Planning Practice in Urban Morocco

Abstract: Sixty in-depth interviews with mothers living in a urban slum of Morocco probed resistances to practicing modern methods of fertility control and began to shed light on some of the reasons family planning programs often fail to reach illiterate target populations. Economic insecurity and the disintegration of the support networks of the traditional extended family complicate the difficult lives of young mothers in the urban slum. While such factors tend to encourage smaller families, the uncertainties and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…''' (1986, p. 57) And one of Mernissi's informants discusses marrying a cousin ''for whom I felt no passion' ' (1989, p. 58), and with whom, because of his impotence-perhaps an indicator that her lack of passion was reciprocated-she ceased to have sex within a few years of marriage. To the extent that sexuality has become an increasingly important ingredient in Arab marital decisions, suggested by Mernissi (1975b), by qualitative accounts of elopement (e.g., Shaaban 1988), and by articles in the popular press (e.g., Braude 2006;Zoepf 2006), it will detract from the appeal of a consanguineous union, especially one between close patrilateral cousins who likely grew up in a shared living space, albeit with the standard male/female boundaries. On the other hand, a person attracted to a more modern type of marriage of this type may also be more likely to value some autonomy, to which the richer social capital associated with consanguinity can contribute.…”
Section: The Flipsidementioning
confidence: 99%
“…''' (1986, p. 57) And one of Mernissi's informants discusses marrying a cousin ''for whom I felt no passion' ' (1989, p. 58), and with whom, because of his impotence-perhaps an indicator that her lack of passion was reciprocated-she ceased to have sex within a few years of marriage. To the extent that sexuality has become an increasingly important ingredient in Arab marital decisions, suggested by Mernissi (1975b), by qualitative accounts of elopement (e.g., Shaaban 1988), and by articles in the popular press (e.g., Braude 2006;Zoepf 2006), it will detract from the appeal of a consanguineous union, especially one between close patrilateral cousins who likely grew up in a shared living space, albeit with the standard male/female boundaries. On the other hand, a person attracted to a more modern type of marriage of this type may also be more likely to value some autonomy, to which the richer social capital associated with consanguinity can contribute.…”
Section: The Flipsidementioning
confidence: 99%
“…Over the last half century, marriage in developing societies has become increasingly arranged by the couple themselves, based in part on mutual desire and an emerging romantic imperative (in sub-Saharan Africa: Bledsoe, 1990; Poulin, 2007; Smith, 2001; arab countries: El Feki, 2013; Mernissi, 1975; Shaaban, 1988; Asia: Ghimire, Axinn, Yabiku, & Thornton, 2006; Riley, 1994). Decadesago, Goode (1963:19) identified the emergence of these “own-choice” marriages as one of the underlying factors driving the fertility transition, linking the two through a widening repertoire of personal choice .…”
Section: Introductionmentioning
confidence: 99%
“…Own-choice marriage as a model has enjoyed increasing appeal throughout the Middle East and North Africa region over the last 40 years (Mernissi, 1975; Shaaban, 1988), especially among university graduates and those identifying themselves as more modern (El-Feki, 2013:32; Hortaçsu and Oral, 1994). As early as the 1920s, Turkey enacted legislative reforms of women’s status, including outlawing polygamy and giving women equal rights in divorce proceedings (Culpan and Marzotto, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Although some researchers (e.g., Freyne & Wrigley, 1996;Schaufeli, 1990) have examined workplace aggression from the perspective of workers who admit to having perpetrated aggression against clients, no studies have been conducted among HCWs in AIDS care in Nigeria. Nevertheless, in various international studies such as those of Jewkes, Abrahams, and Mvo (1998) in South Africa, Jeffery, Jeffery, and Lyon (1989) in North India, Mernissi (1975) in Morocco, and Sargent and Bascope (1996) in Jamaica, the authors have reported that, in order to assert their authority and to control patient behaviors, nurses in public-health settings have employed humiliation, verbal coercion, and even physical violence.…”
mentioning
confidence: 99%
“…Unfortunately, in the existing literature researchers have reported that patient abuse is a serious problem in most developing countries (Jeffery et al, 1989;Mernissi, 1975;Sargent & Bascope, 1996). Patient abuse is considered not only unethical, but as forming a barrier to achieving quality health care and efficient service delivery.…”
mentioning
confidence: 99%